2021
DOI: 10.1101/2021.03.27.437322
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell motion of magnetotactic bacteria in microfluidic confinement: interplay between surface interaction and magnetic torque

Abstract: Swimming microorganisms often experience complex environments in their natural habitat. The same is true for microswimmers in envisioned biomedical applications. The simple aqueous conditions typically studied in the lab differ strongly from those found in these environments and often exclude the effects of small volume confinement or the influence that external fields have on their motion. In this work, we investigate magnetically steerable microswimmers, specifically magnetotactic bacteria, in strong spatial… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
1
2
0
Order By: Relevance
“…While we observed that the geometry of the confinement affects structure formation to a greater extent, a recent study has demonstrated that reorienting torques at walls in numerical simulations are crucial to faithfully reproduce experimental observations of magnetotactic bacteria in circular traps [115]. We note that the parameters chosen in that study are similar to the ones presented in this thesis.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…While we observed that the geometry of the confinement affects structure formation to a greater extent, a recent study has demonstrated that reorienting torques at walls in numerical simulations are crucial to faithfully reproduce experimental observations of magnetotactic bacteria in circular traps [115]. We note that the parameters chosen in that study are similar to the ones presented in this thesis.…”
Section: Discussionsupporting
confidence: 63%
“…Typically, active particles are confined by different geometries during experiments like microtraps (circular) [115] or channels and chambers in microfluidic devices (squared). To investigate the effect of confinement on structure formation in small systems, we varied both the geometry and the type of interactions between the particle and the confining walls in this section.…”
Section: Influence Of Confinement On Structure Formationmentioning
confidence: 99%
“…This single-cell heterogeneity may be suppressed if only population averages are considered. However, long-term tracking of the same individual was not possible until very recently [11,7,12].…”
Section: Introductionmentioning
confidence: 99%